HYPERLIPIDEMIA IS A DOMINANT RISK FACTOR FOR CORONARY HEART DISEASE: Hiperlipidemia Merupakan Faktor Risiko Dominan Kejadian Penyakit Jantung Koroner - I Made Sudarma Adiputra; Ni Wayan Trisnadewi; Ni Putu Wiwik Oktaviani; Dewa Putu Dwita (Jurnal Berkala Epidemiologi, 2023)
Background: Coronary heart disease (CHD) is a major health problem in developed and developing countries. Until now, the death rate due to CHD is the highest in the world. Its risk factors include major modifiable risk factors, such as hyperlipidemia, hypertension, diabetes mellitus, obesity, smoking, and non-modifiable risk factors. Purpose: This study aimed to determine the major risk factors for the incidence of CHD. Methods: This study employed an unmatched case-control design, with a total sample of 43 cases and 86 controls recruited by a purposive sampling technique. Case samples were CHD patients diagnosed by a cardiologist and control samples were non-CHD patients who visited the cardiac polyclinic, with similar variables of age, sex, and residence. The samples were taken at the integrated heart center of Sanglah Hospital, Denpasar, based on the patient medical records. Data analysis was performed using the Chi-square test and logistic regression. Results: The results showed three risk factors that statistically and significantly increased the incidence of CHD, namely history of total cholesterol of â‰¥240mg/dl with adjusted OR=4.64 (95% CI: 1.60-13.49), type-2 diabetes mellitus with adjusted OR=2.85 (95% CI: 1.16-6.99), and smoking with adjusted OR=2.54 (95% CI: 1.01-6.46). Conclusion: The history of high total cholesterol is statistically the most dominant risk factor for the incidence of CHD.